Meaning of Social Entrepreneurship and Socio- Entrepreneurship: An Inquiry Through Mapping The Conceptual Criteria - Wiguna, Atu Bagus; Ananda, Candra Fajri; Susilo (Jurnal Aplikasi Manajemen, 2015)
The study aims to map the criteria of Social Entrepreneurship and socio-entrepreneurship. Data collected through literature survey such as books or scientific articles and analyzed by coding procedure. The criteria of the concept construct a different meaning of individual idea where it depends on the perspective. For social entrepreneurship, economic is a primary perspective and idea is implemented economically. On the other side, Socio-entrepreneurship has social as the primary perspective and the idea implemented socially. The article contributes to the meaning of Social Entrepreneurship and socio-entrepreneurship. However, idea and perspective is latent thing that exist in the way of individual thinking. Therefore, further research need to find out how the individuals implement their idea and perspective in the value creation process into reality.